Insights into molecular structure, genome evolution and phylogenetic implication through mitochondrial genome sequence of Gleditsia sinensis - Hongxia Yang (Nature Portfolio, 2021)
Abstract Gleditsia sinensis is an endemic species widely distributed in China with high economic and medicinal value. To explore the genomic evolution and phylogenetic relationships of G. sinensis, the complete mitochondrial (mt) genome of G. sinensis was sequenced and assembled, which was firstly reported in Gleditsia. The mt genome was circular and 594,121 bp in length, including 37 protein-coding genes (PCGs), 19 transfer RNA (tRNA) genes and 3 ribosomal RNA (rRNA) genes. The overall base composition of the G. sinensis mt genome was 27.4% for A, 27.4% for T, 22.6% for G, 22.7% for C. The comparative analysis of PCGs in Fabaceae species showed that most of the ribosomal protein genes and succinate dehydrogenase genes were lost. In addition, we found that the rps4 gene was only lost in G. sinensis, whereas it was retained in other Fabaceae species. The phylogenetic analysis based on shared PCGs of 24 species (22 Fabaceae and 2 Solanaceae) showed that G. sinensis is evolutionarily closer to Senna species. In general, this research will provide valuable information for the evolution of G. sinensis and provide insight into the phylogenetic relationships within the family Fabaceae.